TINGKAT PENGETAHUAN SISWA DAN SISWI SMP MUHAMMADIYAH 8 DI KOTA MEDAN TERHADAP PENYAKIT HIV AIDS - REZA WIETARA HARAHAP; SHAHRUL RAHMAN (LP2MTBM MAKARIOZ, 2023)
AIDS is a disease caused by the Human Immunodeficiency Virus (HIV) retrovirus and is characterized by an immunosuppressive condition that triggers opportunistic infections, secondary neoplasms, and neurological manifestations. Problems related to adolescent reproductive health and behavior, namely the increase in cases of sexually transmitted diseases, especially AIDS, caused by the HIV virus. Very few adolescents have adequate and correct knowledge about STIs (sexually transmitted infections), including HIV AIDS. Most cases of HIV AIDS infection are starting at the age of 15-39 years with the highest risk factors for HIV AIDS transmission in people with heterosexual behaviorThe type of research used in this study is descriptive quantitative with sratified random sampling. From the results of the study, it was found that the level of good knowledge based on gender was found in the female gender, namely 32 people (47.8%), the level of knowledge based on age had good knowledge was the 16 year age group as many as 5 people (100%), and the level of good knowledge based on the level of education at SMP level III as many as 25 people (45.5%). Good knowledge levels were found for female sex, by age at 16 years old, and at education level at level III of elementry grade.